The Importance of Indirect Hemagglutination Test in the Diagnosis of Cystic Echinococcosis: Serological– Histopathological Correlation - Yülek, Özden; Genç Bahçe, Yasemin; Demir, Hale (Cerrahpaşa Medical Journal, 2023)
Objective: We aimed to determine the reliability of indirect hemagglutination test and its relationship with cyst characteristics in cystic echinococcosis. Methods: The study included 275 cases with indirect hemagglutination test requisition in Siirt; 23 of them were histopathologically examined and 17 of them were diagnosed as cystic echinococcosis. Indirect hemagglutination values (positive: ≥1/160 titrations) and patient and cyst characteristics were recorded. Accuracy rate, sensitivity, and specificity of the indirect hemagglutination test were calculated by comparing the histopathological diagnosis. The relationship between indirect hemagglutination titers and cyst characteristics was investigated. Results: Seventeen cases had cystic echinococcosis diagnosis by indirect hemagglutination test and/or histopathology. Female : male ratio was 1.8 : 1 (P < .003), and mean age was higher in women (29.5) than in men (14.1) (P < .031). There was only 1 false-negative case in the indirect hemagglutina- tion test. The accuracy rate, sensitivity, and specificity of the indirect hemagglutination test for detecting cystic echinococcosis were 96%, 94%, and 100%, respectively. The most common cyst localization was the liver (58.8%). Among indirect hemagglutination-positive cases, the largest cyst had the highest indirect hemagglutination titration. Liver-located cases had the highest titration level, while lung-located ones had the lowest. The lowest titration level was only seen in the cases with a single cyst, while most cases with the highest titration level had multiple cysts. Conclusion: Cystic echinococcosis is a common public health problem especially in eastern Turkey. Indirect hemagglutination is a reliable, practical, and inexpensive method for both diagnosis and follow-up. We presented the first study that deals with the data of Siirt regarding cystic echinococ- cosis, but large-scale studies are needed for more information. Cite this article as: Yülek Ö, Genç Bahçe Y, Demir H. The importance of indirect hemagglutination test in the diagnosis of cystic echinococcosis: Serological–histopathological correlation. Cerrahpaşa Med J. 2023;47(2):129-134.